The relationship between self-perception of ability and actual ability in parkinsonian patients performing motor tasks: A prospective study - Joint, C; Fletcher, C; Foxcroft, D; Aziz, T (2010)
Despite an increasing awareness of the nonmotor features of Parkinson disease (PD), it remains common for disability to be measured primarily in terms of motor impairment in these patients. The effect of dopamine on mood and emotion in PD is well known, but the extent to which the patient's perception of his or her ability to carry out motor tasks is a true reflection of their actual ability has not been studied. To investigate this important aspect of PD, we assessed the ability to carry out timed motor tasks during a levodopa challenge test in 36 PD patients and used visual analogue scales (VASs) to measure self-perception of "onYoff" state and of physical ability. We also recorded aspects of mood on the VAS to see whether these were relevant in relation to the patients' perception. The levodopa challenge test involves assessing patients in both an "off medication" and "on medication" state and so allowed us to observe the patients throughout the range of states of PD that they may experience during the day. Most patients' perception of their motor ability fairly accurately reflected their actual ability on the timed motor tasks throughout the levodopa dose cycle during the levodopa challenge test; however, 5 patients were disproportionately pessimistic about their ability when in the "off" medication state. These patients recorded worse scores on the VAS for aspects of mood and were also taking their PD medication doses more frequently than were the other patients. A better understanding of the patients' perspective of their disability could lead to improved care for PD patients in general and also has implications for our management of patients following surgical procedures, such as deep brain stimulation, that predominantly improve motor symptoms. Copyright © 2010 American Association of Neuroscience Nurses.